Analisis Windrose untuk Prediksi Arah & Jangkauan Pencemaran Udara - Suryana, I Gede Putu Eka (INFOTEKS (Information Technology, Computer and Sciences), 2022)
Human activities are increasingly complex so that it can cause pollution in both water, soil and air. Pollution that occurs in the air gets more attention in this case. A pollutant emitted by the source will undergo a process of transportation and transformation in the atmosphere. Meteorological factors such as air temperature, humidity, wind direction and speed, atmospheric stability, and rainfall contribute to the transportation process. The purpose of this research is to determine the extent of the range of pollutants caused by the smoke of a factory and also to predict the direction of these pollutants. The method used to analyze the measurement data is the wind rose method or Windrose. Windrose is a method of describing information about the speed and direction of the wind at a certain location. Wind roses are depicted in a circular format with a schematic of the frequency of the wind blowing from a certain direction as a representation of meteorological data, especially in the study of air pollution, because it can be seen the direction of the furthest distribution of pollutants and the maximum range of these pollutants. The results showed the difference between morning and afternoon, both from meteorological conditions in terms of air temperature, wind speed, humidity and dominant wind direction so that it affected the ability to lift particles. Areas that are safe from pollution are north, southeast, southwest, west can be recommended as residential locations.